2009
DOI: 10.7182/prtr.19.2.f6h6535591137258
|View full text |Cite
|
Sign up to set email alerts
|

Constantly responsible, constantly worried, constantly blessed: parenting after pediatric heart transplant

Abstract: The parents described their experiences in positive terms, yet acknowledged hardships. Key themes included (1) constantly responsible, (2) constantly worried, (3) constantly blessed, and (4) coping with life. The identified themes provide direction for interventions to help parents cope with the experience of parenting a child after heart transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…For instance, parents stated that "transplant is not a cure but a treatment, " as they still experience different types of medical interventions and treatments after the transplant. Unlike the previous studies that indicate the constant nature of the responsibilities and worries of parents of children with an organ transplant (Anthony et al, 2010a;Anthony et al, 2010b;Green et al, 2009;Lerret et al, 2014;Tong et al, 2010), the parents in this study often used a positive tone when describing their "tough" experiences meeting their children's medical and developmental needs. Many parents described in great detail how they had addressed posttransplant treatments and adjustments to their new lifestyles.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, parents stated that "transplant is not a cure but a treatment, " as they still experience different types of medical interventions and treatments after the transplant. Unlike the previous studies that indicate the constant nature of the responsibilities and worries of parents of children with an organ transplant (Anthony et al, 2010a;Anthony et al, 2010b;Green et al, 2009;Lerret et al, 2014;Tong et al, 2010), the parents in this study often used a positive tone when describing their "tough" experiences meeting their children's medical and developmental needs. Many parents described in great detail how they had addressed posttransplant treatments and adjustments to their new lifestyles.…”
Section: Discussionmentioning
confidence: 85%
“…Although stress is often associated with raising a child with a disability or chronic illness, research employing qualitative (Green, Meaux, Huett, & Ainley, 2009;Tong, Lowe, Sainsbury & Craig, 2008;Tong, Lowe, Sainsbury, & Craig, 2010), quantitative (Glenn, Cunningham, Poole, Reeves, & Weindling, 2009), and mixed methods (Hall et al, 2012;Ylven, Bjorck-Akesson, & Granlund, 2006) has discovered that stress does not always lead to negative family outcomes. For instance, when describing difficulties in meeting their children's special healthcare needs, parents of children with pediatric heart transplants also expressed the blessings of having these children in their lives (Green et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing— Green et al (2009) completed an ethnographic study centering on parents' perceptions of caring for a child who has had a heart transplant. Four themes emerged with one of them being titled “constantly blessed.” This theme included statements that the parents were thankful to still have their child alive and present with them.…”
Section: Resultsmentioning
confidence: 99%
“…The families' adjustment to accommodate needs of the transplant child is multifaceted and places additional strains on the family routines (Denny et al, 2012). Similarly, caregivers of adult transplant recipients reported a desire for life before the chronic illness as a sense of security (Beckmann et al, 2016) and parents of heart transplant recipients have described the importance of normality (Green, Meaux, Huett, & Anley, 2009). Paying attention to child and family adjustment after SOT continues after the 6-month time period included in this study, as it has been reported to be an important concern 2-3 years after transplant (Brosig et al, 2014).…”
Section: Theme 3: "Facing a Future"mentioning
confidence: 99%